Comparison of the innate immune responses of porcine monocyte-derived dendritic cells and splenic dendritic cells stimulated with LPS. Issue 3 (April 2015) - Qu, Xueqi; Cinar, Mehmet U; Fan, Huitao; Pröll, Maren; Tesfaye, Dawit; Tholen, Ernst; Looft, Christian; Hölker, Michael; Schellander, Karl; Uddin, Muhammad J
Dendritic cell (DC) subsets form a remarkable cellular network that regulate innate and adaptive immune responses. Although pigs are the most approximate model to humans, little is known about the regulation of monocyte-derived DCs (moDCs) and splenic DCs (SDCs) in the initiation of immune responses under inflammatory conditions. We investigated the activation and maturation of porcine moDC and SDC subpopulations following LPS stimulation. Porcine monocytes that would differentiate into moDCs were isolated. SDCs were isolated directly from the porcine spleen. Following LPS stimulation, phagocytosis activity, TLR4/MyD88-dependent gene expression, co-stimulatory molecule, and pro-inflammatory cytokine (TNF-α, IL-1β) and chemokine (IL-8) expressions were increased in both cell subsets. Furthermore, moDCs showed higher levels of gene and protein expression compared with SDCs. Interestingly, moDCs were found to be more responsive via the TLR4/TRAF-dependent signalling pathway of activation. Only SDCs expressed higher level of IL-12p40 gene and protein, whereas, IFN-γ gene and protein expression were likely to be unchanged after LPS stimulation in both cell subtypes. These data demonstrate that porcine moDCs display a greater ability to initiate innate immune responses, and could be used as a model to investigate immune responses against Ags.